The role of pancreatic insulin secretion in neonatal glucoregulation. I. Healthy term and preterm infants. Issue 3 (March 1993) - Hawdon, J M; Aynsley-Green, A; Alberti, K G; Ward Platt, M P
Abstract : The glucoregulatory role of insulin in adult subjects is undisputed. However, less is known about the secretion of insulin and its actions in the neonatal period, either for healthy subjects, or for those at risk of disordered blood glucose homoeostasis. The relationships between blood glucose and plasma immunoreactive insulin concentrations were therefore examined in 52 healthy children (aged 1 month-10 years), 67 appropriate birth weight for gestational age (AGA) term infants, and 39 AGA preterm neonates. In children and AGA neonates, plasma immunoreactive insulin concentration was positively related to blood glucose concentration. However, although both groups of neonates had significantly lower blood glucose concentrations than children, plasma immunoreactive insulin concentrations were significantly higher in both term and preterm neonates, when compared with children. The variation in plasma immunoreactive insulin concentrations was greater for neonates than for children. These data suggest, that compared with older subjects, plasma immunoreactive insulin concentrations are high in newborn babies and that neonatal pancreatic insulin secretion is less closely linked to circulating blood glucose concentrations. There are important implications for the interpretation of studies in hypoglycaemic and hyperglycaemic neonates.